2016
DOI: 10.1177/0300985816653989
|View full text |Cite
|
Sign up to set email alerts
|

Splenitis in 33 Dogs

Abstract: Splenitis is uncommonly reported in dogs. Herein, the authors describe its prevalence, clinical findings and outcomes, histologic patterns, and causes. Splenic samples of dogs diagnosed with splenitis between 2005 and 2013 were collected and stained with hematoxylin and eosin, Gram, green-Gram, Giemsa, periodic acid-Schiff, and Ziehl-Neelsen. Samples were processed for polymerase chain reaction (PCR) to detect bacteria, fungi, and protozoa ( Leishmania infantum, Hepatozoon canis). Thirty-three of 660 splenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
1
15
0
4
Order By: Relevance
“…In the present study, PCR testing identified four dogs infected with B. canis and, interestingly, all of them were diagnosed with HSA. On the other hand, a potential causative role in the development of splenitis has been attributed to the presence of mesenchymal neoplastic diseases [22]. As previously described, HSA could predispose to alter the splenic vasculature, thrombosis, and abnormal blood flows, possibly favoring bacterial engraftment [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, PCR testing identified four dogs infected with B. canis and, interestingly, all of them were diagnosed with HSA. On the other hand, a potential causative role in the development of splenitis has been attributed to the presence of mesenchymal neoplastic diseases [22]. As previously described, HSA could predispose to alter the splenic vasculature, thrombosis, and abnormal blood flows, possibly favoring bacterial engraftment [40].…”
Section: Discussionmentioning
confidence: 99%
“…described infiltration of perivascular mononuclear cells into the spleen, more severe for ehrlichial infections [21]. Leishmania infantum and Hepatozoon canis were identified in the spleen of dogs with splenitis [22]; and progressive spleen architecture breakage in visceral leishmaniosis was characterized by disorganization of the white pulp, associated with a more frequent and intense plasma cell accumulation in this organ, mostly in dogs with high parasite density [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Ferri et al . recently observed that 32 of 33 cases of splenitis were caused by an infectious agent (Ferri and others 2016). The majority of infectious cases were from bacterial splenitis, with Pseudomonas species being the most common bacterial agent.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of infectious cases were from bacterial splenitis, with Pseudomonas species being the most common bacterial agent. The remaining cases of infectious splenitis were secondary to systemic mycoses, leishmaniasis or hepatozoonosis (Ferri and others 2016). An underlying cause for splenic inflammation could not be found for one case, leading to a diagnosis of primary splenitis (Ferri and others 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation